PENGARUH LATIHAN FARTLEK TERHADAP DAYA TAHAN AEROBIK TIM FUTSAL KELUARGA KITA 217 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is that the endurance of the Aerobics of Futsal Keluarga Kita 217 Pekanbaru athletes is still less than optimal, seen during the second half the players began to experience fatigue, unable to regulate breathing, skills, teamwork began to be invisible so that the ball was easy seized by the opponent and attacked players Futsal Keluarga Kita 217 Pekanbaru players slowly descended into their own area. To fix this problem, the writer gives a form of exercise that increases aerobic endurance, namely Fartlek training. The title raised in this study is "effect of fartlek training on aerobic endurance on Futsal Keluarga Kita 217 Team Pekanbaru" so that in the future the team has good aerobic endurance, and the most important thing after this research is knowing whether there is an increase in endurance especially aerobic endurance. The form of this research is (using a one group pretest-posttest design approach) with a population of Futsal Keluarga Kita 217 Team Pekanbaru totaling 10 people. The instrument used in this research was to use the Aerobic test which aims to determine the effect of Fartlek training on Aerobic endurance. After that, the data is processed statistically, to test normality using the lilifours test at a significant level of 0.05α. The hypothesis proposed is that there is an effect of fartlek training on aerobic endurance on Futsal Keluarga Kita 217 Team Pekanbaru. Based on the analysis of the normality of the data X, it produces a Lhitung of 0.153 and a Ltable of 0.258, which means that Lhitung <Ltable. while Y variable yields Lhitung of 0.159 and Ltable of 0.258 means that Lhitung <LTabel then the data is normally distributed. Based on statistical data analysis, there is an average variable X of 1.98 and an average variable Y of 2.54. Then obtained a tcount of 2.59 and ttable of 1.812 then tcount> ttable then Ha is accepted. Thus it can be concluded that there is an effect of fartlek training on aerobic endurance on Futsal Keluarga Kita 217 Team Pekanbaru.Keywords: Fartlek Training, Aerobic Endurance